Da problemática do discurso à semiótica discursiva: uma análise das decisões judiciais do caso Lula - Venâncio, Rafael (2021)
In the wake of the recent history of Brazilian politics, events of a discursive order often gain notoriety due to their capacity to reverberate and introduce discussions relevant to society in general; in addition, the uniqueness of the events mentioned more often than not highlights the emergence and role of the language sciences in explaining and reflecting on them, bringing answers to the concerns caused by such events. This is the case of the habeas corpus filed in favor of former President Lula, in 2018, in which he sought, together with the on duty judge of the Federal Regional Court of the 4th Region, to free the prisoner, imprisoned because of the conviction, in the second degree of jurisdiction, for the alleged crimes of passive corruption and money laundering. Rogério Favreto, a judge on duty, understanding that there was legal plausibility, granted the request and ordered the release of the former President of the Republic from the Paraná Federal Police. However, the order was not carried out due to interference from the then first degree judge, Sérgio Moro, who, claiming that Favreto was not competent to order the release of Lula, recommended that the agents wait for another magistrate to pronounce on the act. Soon, a simple habeas corpus deferment became, that day, the space for a battle of the togas, led by 4 magistrates, each one determining that the condemned man should be released/ apprehended, producing, in that dispute, 6 judicial decisions, which are the corpus of this dissertation. In this context, our research, in a connection between the Greimasian discursive semiotics and the Law, intends to investigate, in the corpus on stage, how the discursive manifestation of the legal-political conflict that governs the habeas corpus case of former President Lula takes place, seeking to discover, at the appropriate time, the axiologies that underlie the decisions in order to order the convict's arrest/release. Results reveal that the axiologies of each magistrate directed the fate of the convict and fed, indeed, the discursive polemic of the event in question.